Estrogen Receptor Alpha Signaling Is Responsible for the Female Sex Bias in the Loss of Tolerance and Immune Cell Activation Induced by the Lupus Susceptibility Locus Sle1b - Jared H. Graham; Shayla D. Yoachim; Karen A. Gould (Frontiers in Immunology, 2020)
The dramatic female sex bias observed in human lupus is thought to be due, at least in part, to estrogens. Using mouse models, we have shown that estrogens, acting through estrogen receptor alpha (ERα) promote lupus development and contribute significantly to the female sex bias observed in this disease. C57Bl/6 (B6) mice carrying the lupus susceptibility locus Sle1 locus exhibit immune cell hyperactivation and loss of tolerance, and the action of Sle1 displays a strong female sex bias. Previously, we showed that disruption of ERα completely eliminates the female sex bias in the effects of Sle1. Here we report that ERα signaling selectively modulates the action of Sle1b, one of the three subloci that together constitute Sle1. We observed that disruption of ERα signaling attenuated T cell hyperactivation, formation of spontaneous germinal centers, loss of tolerance, and the development of anti-chromatin autoantibodies in B6.Sle1b female mice, but had no impact on these phenotypes in B6.Sle1b male mice. In fact, disruption of ERα completely abolished the female sex bias that is seen in each of these phenotypes in B6.Sle1b mice. Strikingly, Sle1b-induced B cell hyperactivation, a female sex-specific manifestation of Sle1b, was completely abrogated by disruption of ERα in B6.Sle1b females. Altogether, these results demonstrate that ERα signaling is responsible for the female sex bias in the actions of Sle1b, and is absolutely required for the female-specific B cell hyperactivation phenotype associated with this lupus susceptibility locus. By contrast, we found that ERα signaling had no impact on Sle1a, the other Sle1 sublocus that exerts effects that show a female sex bias.